Penggunaan Video Animasi Sebagai Sarana Edukasi Bagi Anak Di Dinas Keluarga Berencana, Pemberdayaan Perempuan Dan Perlindungan Anak - Zulfa, Ira; S, Richasanty Septima; Humaira, Ainun (Jurnal Teknik Informatika dan Elektro, 2024)
Education is a conscious and planned effort to develop the potential of students to have spiritual strength, self-control, personality, intelligence, noble character, and necessary skills. Educational technology, especially multimedia such as animated videos, has great potential in improving the effectiveness of learning. However, in Central Aceh, the use of animated videos as a means of education in socialization activities is still limited. This research limits the focus to the use of animated videos as a means of education for children in the Family Planning, Women's Empowerment and Child Protection Office in Central Aceh. The problem formulation includes questions about the feasibility of using animated videos as a learning medium and their effectiveness in socialization activities in villages. The purpose of this study was to evaluate the feasibility of using animated videos as a learning medium and measure their effectiveness in socialization activities in Central Aceh villages. The results of the study are expected to provide new insights on the use of animated videos in the context of education in Central Aceh, as well as provide recommendations for the Family Planning, Women's Empowerment and Child Protection Office to improve the quality of socialization through innovative learning media.